Pendidikan Tinggi dan Budaya Mutu STAI Babussalam Sula Maluku Utara - Umasugi, Hamzah; Gorontalo, Rifani (Sekolah Tinggi Agama Islam Babussalam Sula, 2025)
This article aims to determine the formation of a quality education system and the relationship between higher education and quality culture. The method used is qualitative with a grounded research approach, namely obtaining data directly and then analyzing the data systematically. Some of the results are that in efforts to improve the quality of education, every lecturer is required to write articles/journals every semester. In the learning aspect, lecturers are also required to innovate as an effort to encourage students to create a culture of quality by including and even involving them in improving quality at STAI Babussalam Sula, North Maluku. To improve the quality of education, various academic and non-academic activities are reflected in innovative teaching approaches, and various forms of guidance and coaching to help students achieve success in their studies and prepare them to face challenges in the professional world after graduation. From the financing side, STAI also always strives to meet every unit's needs and can deliver a harmonious financial reporting system from bottom to top.